A Comparative Analysis of the Determinants of Risk and Performance in Chinese and UK Banks - Wei, Yaqi (2018)
Driven largely by the recent financial crisis and accounting standards, the performance of banks and its risk have received increasing attention especially in the banking sector. Focusing on how well the bank could perform after the strike of financial crisis and how much they put attention to risk management, this study provides insights on determinants of a bank’s performance and risk of a sample of UK and Chinese banks for the examined year from 2007 to 2017 following the adoption of Basel III. Using the hypotheses tests and multivariate regression model, appropriate models were chosen for evaluating bank performance and bank risk and then potential relationships between determinants were examined. The finding reveals that Chinese banks have a better performance in avoiding negative outcomes from financial crisis than that of UK banks while UK banking system put much attention to risk preparation. Corresponding suggestions were raised in order to help two countries overcome the obstacle from financial crisis.